ESMIS--a computer-based emergency medical services management information system. Part 2. Database design - Shahein, H I; Zaky, M M (International journal of bio-medical computing, 1984)
In this paper, the emergency medical services system of a health care organization are investigated. The result of this investigation is an on-line Emergency Medical Services Management Information System (ESMIS). ESMIS is implemented using the TOTAL database management system. Reports illustrating the system's performance are also provided. Part 1 (this issue) outlined the ESMIS design procedure, while part 2 is concerned with the specifications of the system's outputs.